The Comparison of Hydrogen Purity on Brown’s Gas Using Dry Cell Electrolyzer with/without Polyvinyl Alcohol (PVA) Separator Membrane - Rahmadina, Nisa; Bow, Yohandri; Yusi, Syahirman (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
Global environmental issues that demand good air quality have encouraged various energy sources to develop environmentally friendly energy. Brown’s Gas is produced by using an electrolysis system to separate water into Hydrogen (H2) and Oxygen (O2) gas. The dry cell is an electrolyzer that is widely used for both small and large-scale hydrogen production systems. A dry cell electrolyzer was designed with 12 stages of 316 stainless steel with Polyvinyl Alcohol as a polymer membrane to prevent mixing H2 and O2 to get a high percentage of hydrogen purity. This study compares hydrogen purity on Brown’s gas using a dry cell electrolyzer with PVA with/without a PVA separator membrane. The result shows that the PVA membrane significantly impacted hydrogen purity. The hydrogen purity on Brown’s gas without PVA membrane for KOH, NaOH, KCl, and Seawater was 58.37%, 56.42 %, 50.16%, and 55.22 %. Compared to using the membrane was 78.32%, 77.80%, 63.16%, and 74.0 %, with the highest hydrogen obtained was KOH electrolyte.